The undertaker's daughter : a memoir - Mayfield, Katherine, 1958- (New York : Gallery Books, 2015)
"Kate Mayfield's first foray into nonfiction is a vivid Southern memoir that reads like a novel, about growing up in Jubilee, Kentucky as the daughter of a charismatic but troubled small-town undertaker--imagine Mad Men's Sally Draper growing up in the world of The Help"--
Keywords: Mayfield, Katherine, -- 1958- -- Childhood and youth; Authors, American -- 21st century -- Biography